Double or Quits? Robbe-Grillet and the Myth of Identity - Voisset-Veysseyre, Cécile (Amaltea. Revista de Mitocrítica, 2011)
A reading of Alain Robbe-Grillet’s text brings up to date the force of a demystifying writing, i.e., which empties the representative content. Under the influence of cinema, a new literary practice emerges, which claims the cutting as a narrative resource of its own in the context of a new novel which challenges self-perception; the ultimate montage defines thus the whole gaming space. If the author is dead, so is autobiography. The writer – the scripter – experiences a modern novelistic form in sharp contrast with linear, traditional narratives. Not only has the self ceased to invent itself, but gets emblematically destroyed in the figure of the shattered mirror. The wandering ghost – that of the double, of the one and the multiple – leads to the textual analysis of an identity which the myth assures.